2014
DOI: 10.1017/s0007114514000737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol alone or in combination with piperine on cerebral blood flow parameters and cognitive performance in human subjects: a randomised, double-blind, placebo-controlled, cross-over investigation

Abstract: Previous research has shown that resveratrol can increase cerebral blood flow (CBF) in the absence of improved cognitive performance in healthy, young human subjects during the performance of cognitively demanding tasks. This lack of cognitive effects may be due to low bioavailability and, in turn, reduced bioefficacy of resveratrol in vivo. Piperine can alter polyphenol pharmacokinetics, but previous studies have not investigated whether this affects the efficacy of the target compound. Therefore, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 38 publications
6
129
1
2
Order By: Relevance
“…Several other studies have attributed the protective effects of resveratrol from stroke to its neuroprotective effects [145][146][147][148][149][150], which have been reviewed previously [151]. Although there is no human clinical trial that investigated the protective effects of resveratrol in stroke patients, a single dose of resveratrol has been shown to increase the cerebral blood flow during a performance task in healthy adult subjects [152,153].…”
Section: Strokementioning
confidence: 99%
“…Several other studies have attributed the protective effects of resveratrol from stroke to its neuroprotective effects [145][146][147][148][149][150], which have been reviewed previously [151]. Although there is no human clinical trial that investigated the protective effects of resveratrol in stroke patients, a single dose of resveratrol has been shown to increase the cerebral blood flow during a performance task in healthy adult subjects [152,153].…”
Section: Strokementioning
confidence: 99%
“…However, this study did not examine whether or not the addition of piperine affects the bioavailability of resveratrol, as they were focused on determining the mechanism of action. In another recent study, Wightman and colleagues demonstrated that piperine can increase the bioefficacy of resveratrol when co-supplemented in healthy human subjects with regard to cerebral blood flow effects [25]. In this study, co-supplementation of piperine and resveratrol were found to significantly augment cerebral blood flow during task performance without affecting cognitive function, mood or blood pressure.…”
Section: Bioavailability Absorption and Metabolism Of Resveratrolmentioning
confidence: 54%
“…It is possible that poor bioavailability could contribute to reduced brain effects in humans (Wightman et al 2012). In a related study, co-supplementation with the pepper alkaloid Piperine, improved resveratrol's effects on CBF during memory task performance compared to placebo and resveratrol alone (Wightman et al 2014). These data indicate that bioefficacy of resveratrol with regard to CBF effects is related to its bioavailability and the same could be relevant to other polypenols.…”
Section: Application Of Polyphenols In Human Cns Disease: Clinical Stmentioning
confidence: 76%